Phase I Study of Anti-GM2 Ganglioside Monoclonal Antibody BIW-8962 as Monotherapy in Patients with Previously Treated Multiple Myeloma. Issue 2 (December 2016) - Baz, Rachid; Zonder, Jeffrey; Gasparetto, Cristina; Reu, Frederic; Strout, Vincent
Abstract Introduction BIW-8962 is a monoclonal antibody to GM2 ganglioside that shows preclinical activity towards multiple myeloma (MM) cell lines and in animal models bearing MM xenografts. The objective of this study was to determine the safety, tolerability, maximum tolerated dose (MTD), pharmacokinetics, potential immunogenicity, and preliminary clinical efficacy of BIW-8962 in patients with heavily pretreated MM. Methods Patients (n = 23) received escalating doses of BIW-8962 (0.03–3 mg/kg) intravenously every 2 weeks in phase Ia. The highest anticipated dose (10 mg/kg) was not tested and the study was discontinued without proceeding to phases Ib and II. Results The MTD of BIW-8962 was not established and BIW-8962 was relatively well tolerated. No pattern of consistent toxicity could be inferred from treatment-related AEs grade ≥3 and only two dose-limiting toxicities were recorded (atrial thrombosis + cardiomyopathy and chest pain, respectively). In the efficacy evaluable population (n = 22), no patient had a response (complete or partial) and 16 (72.7%) had a best response of stable disease, which was generally not durable. Conclusion BIW-8962 did not show evidence of clinical activity. The study was therefore stopped and further development of BIW-8962 in MM was halted. Funding This work was funded by Kyowa Kirin Pharmaceutical Development, Inc. Trial registered ClinicalTrials.gov identifier, NCT00775502.